PENGUJIAN RESPONS PERTUMBUHAN BEBERAPA VARIETAS PADI SAWAH (Oryza sativa L.) AKIBAT CEKAMAN SALINITAS - Herti Folarida Hutajulu; Rosmayati Rosmayati; Syafruddin Ilyas (Universitas Sumatera Utara, 2013)
Growth Response Testing of Several Rice Varieties (Oryza sativa L.) Caused of Salinity. In theSub-District Percut Sei Tuan there are around 700 hectares more area paddy fields that can becategorized as has been affected by sea water (is 1-2 km to coast). The production rice fields in thearea was around 2-3 tons per hectare with using varieties Ciherang and Mekongga. But varietiesCiherang have potential result8.5 tonnes/ha with result average 6.0 tonnes/ha in the non- salinity.The problem is to be a basic idea how to increase production the be examined back some varietiesthat had been found varieties that not only could but critical market result in standard national resultrice that is 6.0 ton/ha.This study aims to determine the growth response of some rice varieties due tosalinity stress. The study was conducted in the Village of Tanjung Rejo, Hamlet Paluh Merbau, Sub-District Percut Sei Tuan, Deli Serdang Regency with altitude of 1.5 meters above sea level in April-September 2012 using a Randomized Block Design with eight varieties of rice plant (Ciherang, IR64 , Lambur, Batanghari, Banyuasin, IR 42, Inpari 10 and Margasari) with 3 replication. Parameter isobserved germination, salt injury, plant height, number of tillers, leaf chlorophyll, leaf area, numberof productive tillers, panicle length, number of grains contains per panicle, number of grains perpanicle empty, grain weight per plot, and 1000 grain weight. The results showed that Ciherangvarieties and Banyuasin is highly tolerant to salinity. Banyuasin and Batanghari production per plothad the highest and lowest are IR 64 varieties and Inpari 10 varieties.Keywords: salinity, varieties, paddy.